G543(P) Young persons rounds: a qualitative study exploring the experiences of adolescents on adult wards. (25th October 2020) - Johnson, R; Connell, J; Otley, S; Travers, M; Ioannou, M; Datt, C; Younis, J
Abstract : Objective: To explore the experiences and identify the needs of young adults and adolescents on adult wards at one teaching hospital; and to formulate interventions that will better meet these needs. Introduction: NICE Evidence 2019 and the RCPCH shows that the needs of young patients are complex and are rarely met comprehensively on adult wards. Young patients are often overlooked (Viner, 2007) and they are at risk of many issues that can have significant effects on their health and wellbeing. Although it is recognised that adolescents do better on adolescent wards than paediatric wards, few studies are aimed at improving their experience on the former. Methods: Patients aged 17–22 were interviewed over two rounds of interviews, each consisting of 4 weeks. Interviews were carried out one-on-one using a semi-structured questionnaire. Interviews in both rounds were analysed thematically, with those in round 2 further audio recorded and transcribed for further analysis. Results: 30 patients were interviewed in total, 14 in the first round and 16 in the second. Key themes included: interactions with patients and healthcare professionals, privacy, age, autonomy, and signposting issues. Suggestions for improvements included facilities such as a designated adolescent common room, computers, reading material and television; as well as emotional support via day-to-day visits, proper signposting and interactive tasks. Discussion: A wide range of experiences both positive and negative were revealed with regards to adolescent care. Adolescent needs were shown to be even more extensive than previously realised, and work is needed to improve how they are met. The findings of this study provide valuable guidance to the improvement of adolescent care at the teaching hospital in which this study was conducted; as well as setting up a structure for similar investigations in other healthcare settings. An adolescent outreach team comprised of volunteers and led by a youth worker could make a vital difference in the provision of emotional support, as well as continuing to gain insight into what improvements most effectively benefit adolescents on adult wards.